Utilization of Instagram Online Shop in Millenial Generations - Putu Cahya Widarma Eka Putra; Nyoman Sri Subawa (Institute of Computer Science (IOCS), 2021)
One of the interesting advances in technological innovation is the emergence of internet technology. Where the development of Instagram is so fast in 2019 that there are many Instagram users for personal gain and for business. This progress has led to distruption so that many personal Instagram accounts and business accounts have emerged for promotional purposes. In carrying out marketing communications, companies must have a strategy so that all predetermined plans can be achieved. A good strategy will provide benefits for the company as the realization of the goals of the company. This study discusses the strategy of using Instagram as a digital marketing communication medium carried out by Mellinial Generation. The method used in this research is a qualitative descriptive method. In addition, this study also uses in-depth interview techniques with 4 resource persons, namely millennial owners from online marketplaces, literature studies and documentation. Based on the results of research and discussion, it is known that planning the use of Instagram is by analyzing problems, analyzing audiences, determining goals, selecting media and communication channels, and developing plans or activities for achieving goals. The use of Instagram as a media for digital promotion is mostly carried out by the millennial generation by utilizing photo and video features, comments, captions, locations, hashtags, tagging and Instagram ads for social media maintenance, as well as followers and likes for social media endorsements. Evaluation of the use of Instagram is the result of increased sales and the success of opening new stores and outlets.